2010
DOI: 10.1590/2175-7860201061129
|View full text |Cite
|
Sign up to set email alerts
|

New combinations in Phanera (Leguminosae; Cercideae) from Brazil

Abstract: Twenty-nine new combinations and one new synonym are proposed in Phanera for species previously treated as Bauhinia. The occurrence of each species in Brazil is noted. The lectotypification of Bauhinia alata and B. radiata is proposed. Phanera alata is illustrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Phanera (Fig. D) was first described as a genus by Loureiro (), and has since been recognised at the generic level by several authors (e.g., De Wit, ; Schmitz, ; Queiroz, ; Vaz, ; Wunderlin, ; Bandyopadhyay & al., ; Kumar & al., ; Mackinder & Clark, ). De Wit () divided the genus into three subgenera and several sections, and Schmitz (), who used this classification in his analysis of the pollen morphology of Bauhinia s.l., remarked that the limits of the genus were imprecise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phanera (Fig. D) was first described as a genus by Loureiro (), and has since been recognised at the generic level by several authors (e.g., De Wit, ; Schmitz, ; Queiroz, ; Vaz, ; Wunderlin, ; Bandyopadhyay & al., ; Kumar & al., ; Mackinder & Clark, ). De Wit () divided the genus into three subgenera and several sections, and Schmitz (), who used this classification in his analysis of the pollen morphology of Bauhinia s.l., remarked that the limits of the genus were imprecise.…”
Section: Discussionmentioning
confidence: 99%
“…Initially recognised as the genus Bauhinia L., Bauhinia s.l. has been the focus of recent phylogenetic studies (e.g., Zhang, ; Hao & al., ; Sinou & al., ; Meng & al., ; Wang & al., ) and of revised classifications and nomenclatural changes (e.g., Lewis & Forest, ; Queiroz, ; Vaz, ; Wunderlin, , ; Bandyopadhyay & al., ; Bandyopadhyay & Ghoshal, , ; Mackinder & Clark, ; Trethowan & al., , Clark & al., ). All of the previous phylogenetic studies have concluded that Bauhinia s.l.…”
Section: Introductionmentioning
confidence: 99%
“…Caulotretus as a second generic section of Schnella. This reclassification came only months after Vaz (2010) had transferred the majority of the same species from Bauhinia sens. lat.…”
Section: Phanera Lour: Taxonomic Rank Generic Limits and Relationshipsmentioning
confidence: 99%
“…Additionally, we consulted major regional treatments such as "A revision of Malaysian Bauhinieae" ; Flora of Thailand (Larsen et al 1984); Flora Malesiana (Larsen & Larsen 1996) and Flora of China (Li et al 2010) as well as papers describing new taxa or publishing new combinations (Thothathri 1965, Schmitz 1977, Vaz 2010, Wunderlin 2011, Bandyopadhyay et al 2012. Consequently, the taxa presented here are based principally on the taxonomy of regional flora treatments.…”
Section: How the List Of Names Was Assembledmentioning
confidence: 99%
“…Thirty two new combinations have already been proposed in Phanera Lour. occurring in the Neotropical region from Brazil (Queiroz, 2006;Vaz, 2010) and for one species from the Palaeotropical region (Wunderlin, 2011). Fifty new combinations are proposed here in Phanera occurring in the Palaeotropical region from China, India and Myanmar to Malesia along with the types of the names which have been cited either by scrutinizing the relevant protologues or from the publication of Larsen and Larsen (1996).…”
Section: Introductionmentioning
confidence: 99%